PENGARUH KONFLIK PERAN DAN AMBIGUITAS PERAN TERHADAP KOMITMEN INDEPENDENSI AUDITOR INTERNAL PEMERINTAH DAERAH (Studi Empiris pada Inspektorat Kota Batam) - Syahdewi, Raja Risma; Hardi, Hardi; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to examine the influence of role conflict and role ambiguity to the government internal auditors’ commitment to independence. Research variables operationally elaborated in several dimensions. Variable commitment to independence elaborated into three dimensions, namely a strong belief in values, a willingness to exert considerable effort, and a strong personal desire. Variable role conflict elaborated into three dimensions, namely inter-role conflict, intra-sender role conflict, and personal role conflict. Variable role ambiguity elaborated into six dimensions, namely guidelines, task, authority, responsibilities, standards, and time. The population of this research is the Batam city Regional Inspectorate officers, who participate in regular inspection as the internal auditor of the government, with the number of 40 officers where all of them became the respondents for this research. The data taken from questionnaires distributed to all respondents. The data were analyze using multiple regression analysis. The results of this research show that (1) role conflict is significantly positively related to commitment to independence of Inspectorate officers and (2) role ambiguity is significantly positively related to commitment to independence of Inspectorate officers.Keyword : Internal Auditing, Role Conflict, Role Ambiguity, and Commitment to Independence